PENGARUH PENGGUNAAN MOBILE BANKING DAN QRIS TERHADAP POLA KONSUMTIF SISWA DI SMA NEGERI 3 SAMARINDA TAHUN 2025 - isna; Umi Fitria; Syaiful Anwar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The rapid development of digital technology has driven significant changes in the consumption behavior of the younger generation, including in schools. One example of this can be seen at SMA Negeri 3 Samarinda, where students have become accustomed to using digital financial services such as mobile banking and QRIS in their daily lives. This study aims to determine the extent to which the use of mobile banking and QRIS influences the consumption patterns of students at SMA Negeri 3 Samarinda in 2025. This study was conducted at SMA Negeri 3 Samarinda using quantitative methods and a survey approach. The research population consisted of 115 students, and 89 respondents were selected using random sampling techniques. Data collection was conducted through questionnaires and documentation, then analyzed using multiple linear regression with the help of SPSS. In linear regression, testing classical assumptions is a crucial step to ensure the accuracy and reliability of the model being built. One form of such testing is the normality test, which aims to evaluate whether the residual difference between the predicted results and the actual values has a normal distribution. The results indicate that: (1) the use of QRIS has a positive and significant effect on students' consumption patterns; (2) mobile banking does not show a significant effect; (3) simultaneously, both variables have a significant effect on students' consumption behavior. These results indicate that access to youth.